Is 911 The Answer? A Retrospective Review of Emergency Medical Services Use by Home Care Providers - Sandra McKay; Emmelie Mohammed; Meghla Roy; Vivian Hung; Matthew Wong; Bonnie Lum; Emily C King (SAGE Publishing, 2023)
With the Ontario healthcare system under strain the use of resources-particularly emergency medical services (EMS) is an increasing focus. Recent work has identified long-term care facilities as high users of EMS despite access to health-related support outside of the hospital. However, such insights are not available for home care. A retrospective review of administrative records of EMS calls drawn from over 6 million visits by home care providers found relatively low call rates: 8.4 calls per 100 000 personal support visits, 4.1 calls per 100 000 for rehabilitation providers, and 0.9 calls per 100 000 for nurses. The majority (85%) of calls resulted in transport to the hospital; the notable exception was fall-related events, and of these falls, a third (32%) were treated at home. Classification of reported physical symptoms suggests opportunities for leveraging in-home clinical specialists to avoid hospital transport where possible and preserve EMS capacity to respond to the most urgent and severe events.